Use of trypan blue as an aqueous tracer dye to investigate hypotony where cyclodialysis cleft is suspected - Khoo, Ying J.; Abdullah, Aulia A. H.; Yu, Dao‐Yi; Morgan, William H. (Clinical & experimental ophthalmology, 2019)
Importance A new method to help diagnose suspected cyclodialysis clefts. Background To study the use of trypan blue stained aqueous flow patterns in diagnosing causes of hypotony where cyclodialysis clefts were suspected. Design A case series in a tertiary care centre. Participants Ten subjects presenting with persistent hypotony and retinal changes. Methods Trypan blue was injected into the anterior chamber. Main Outcome Measures The pattern of dye flow in the anterior chamber was categorized. Intraocular pressure prior to surgery was recorded. Results All seven subjects with cyclodialysis clefts had a preferential flow to the cleft region. Two hypotonous subjects post trabeculectomy had rapid (5 seconds) and extensive lymphatic staining (6 o'clock hours extent) without visible bleb formation. Conclusions and Relevance Preferential flow of dye to the limbus is a reliable sign of cyclodialysis cleft and helps localize cleft extent. A new cause of hypotony, “lymphatic overdrain,” is identified.